Characterization of spatial variation of indoor coverage for HDTV in Singapore (part 2 hardware) - Muhammad Muhd Muniruddin Mohd Khairuddin (2011)
The planning for digital high definition Television (HDTV) in Singapore will require a good knowledge of the characteristics of digital TV signals indoor especially in HDB estates. This project will study parameters required for the planning like wall penetration losses, spatial variation of signals and multipath delays. Singapore is a cosmopolitan city with high rise buildings abound with trees and tropical vegetation. Its unique conditions pose challenges to broadcasters for providing good service coverage uniformly throughout the island, especially to indoors, which is more complicated than outdoor. Problems like, reflections and diffractions by nearby high-rise buildings and high penetration loss through walls would result to receiving low signal strengths. The placement of antenna in indoor is very important as the received signal varies amplitude significantly over a short distances indoor. Studies to understand the problems cause are required to understand on how digital TV broadcast without losing the signals. Laika TV receiver together with the respective software’s provided are used to obtain parameters such as signal strength, which are important in the study of spatial variation. These equipments send the data collected to the laptop in the form of screen captures and real-time data logging. The results obtained are then plotted and a detailed analysis of the signal variation was done. The performance of the antenna was also analyzed. This final year report will discuss the theories required for this project, the equipments used, results and discussion and lastly, the conclusions and future developments which can be implemented for future studies.